Does oil prices shock matter in the Nigerian economy? Empirical evidence from sign-identified Structural Vector Autoregression - Nazifi Aliyu; Z. S. Saheed; A. A. Alexander; Nafiu B. Abdulsalam (West African Journal of Monetary and Economic Integration, 2018)
This study explores the dynamic linkage of exogenous oil shock and economic activity in Nigeria in Nigeria via a sign- identified Structural Vector Autoregression (SVAR). Specifically, the study utilizes quarterly time series data where the information set uses real gross domestic product, quantity of petroleum demand, exchange rate, interest rate, GDP deflator and inflation rate. We adopt a combination of sign and zero restriction as the identification scheme to impose restrictions in the model. Structural inferences are deduced from structural impulse response function, forecast error variance decomposition and historical decomposition. Findings from structural impulse response function indicates that real gross domestic product react instantaneously, although short-lived, following a unit standard deviation change in oil shock while exchange rate and other variables of interest react, slowly and insignificantly, with several lags after shock initialization. Additionally, it is evident from historical decomposition that fluctuations in real GDP is jointly explained by oil demand and supply shock, with the former exacting more influence than the latter. Recommendations are in two-folds; policies that are shock-absorbing must be strengthened and macroeconomic policies should be formulated that will look into other sources of macroeconomic fluctuations other than oil shocks.
Keywords: C32; E44; G12; G15; 330; SVAR; sign-identification; structural shocks and Impulse response function